The Soleimani effect: a risk for small states in Europe. Issue 6 (31st December 2021) - Veebel, Viljar; Ploom, Illimar; Sliwa, Zdzislaw
ABSTRACT: The assassination of Iranian General Qasem Soleimani by the United States has initiated debates about its reverberations on regional and global security. While it could have been a rational policy by the United States on the national level, this action has carried along innovative features defining what is a legally acceptable self-defence that international law would also accommodate. Namely, if the United States can unilaterally and retroactively interpret the meaning of international law in such a way, there are other powers like Russia or China who may wish to take advantage of such a tactic and expand the formerly relatively stable meaning of law unilaterally in line with their own national interests. Russia has previously given high importance in following the Western path and precedencies, so even when the current thesis is hypothetical and with high odds in upcoming years, it is worthy of consideration and probability analysis.